Metronidazole thermogel improves retention and decreases permeation through the skin - Elayne Karine Souto de Melo; Thalita Pedon de Araujo; José Wellithom Viturino da Silva; Stephanye Carolyne Christino Chagas; Danilo César Galindo Bedor; Davi Pereira de Santana; Leila Bastos Leal (Brazilian Journal of Pharmaceutical Sciences, 2017)
ABSTRACT Metronidazole (MTZ) is widely used as the standard antibiotic for the treatment of rosacea and, more recently, is being used off label in Brazilian hospitals for the treatment of wounds. Following oral administration, minimal amounts of active agent reaches the skin and side effects are strongly induced. Consequently, MTZ is currently being applied topically in order to improve the therapeutic efficacy with reduced side effects, with Rozex(r) (RZ) (an MTZ gelled formulation) being the only marketed product. This study examined whether the use of MTZ 0.75% from thermogel formulations could improve drug retention and reduce dermal exposure compared to that by Rozex(r). Following a 21 h permeation study, the highest total amount of MTZ permeated through the rat healthy and disturbed skin was seen with Rozex(r), but similar to all formulations regardless of the skin condition. On the other hand, the amount retained in the epidermis/dermis was larger for thermogel formulations; at least 4 fold that of Rozex(r), when the stratum corneum was present as a barrier. In conclusion, thermogel formulations can be favorable alternatives to Rozex(r) for the topical application of MTZ with improved efficacy and reduced side effects.